BODY AT STAKE SOCIALIZE BY THE LE PARKOUR: FROM THE TRAINING TO THE ECSTASY FROM THE EQUILIBRIO. (Fiep Bulletin - online, 2014)
The sports of risk well calculated provokes the fascination on the practitioners´s imagination, and is present in daily life. The present paper has an objective to discuss the body risk during the practice of Le Parkour. To do that, we tried to understand the body according to the perspective of nature, that is seen as something dangerous and offensive by civilization, and has to be dominated, domesticated, diminished. From this point on, we tried to understand the risk of the body of the practitioners of the Le Parkour that move rapidly in different direction and directions. The sport began during the 80´in France when two young guys decided to put in practice what they have learned in gym classes and in martial arts through the streets os rue de Lisse. The study of qualitative nature analysed discourses from the internet of practitioners in the Orkut site from communities from Caxias, Ilha do Governador, Florianópolis, Tobu in Rio de Janeiro by means of the technic of AD de Eni Orlandi (2003). In the first analysis , the speeches give us some glues that the practice of Parkour means a way to open other ways in the urban area of big cities, and means that to win the fear, to these practitioners, transcend the necessity of domination of technics of of movements of self-superation. The concentration and the repetition in low obstacles during the movements seem to be the basis of training of bodies and mind..
Keywords: body; risk; Le Parkour